Preparation, characterization and immobilization of silver nanoparticles with horseradish peroxidase: its future aspects in biosensor applications / Zoheb Karim and Rohana Adnan - Karim, Zoheb; Adnan, Rohana (2012)
Several new types of carrier and technology have been implemented in the recent past to improve traditional enzyme immobilization which aim to enhance enzyme loading, activity and stability in order to reduce the cost of enzyme in industrial processes and in sensing technology. Thus, the present study aims to work out a simple and high yield procedure for the immobilization of horseradish peroxidase on silver nanoparticles. FTIR, UVVis and TEM were used to characterize the silver nanoparticles. The single cell gel electrophoresis (comet assay) was also performed to confirm the genotoxicity of silver nanoparticles. To decrease the toxicity of silver nanoparticles, β-cyclodextrin was used as support. A comparative stability study of soluble and immobilized enzyme preparations was investigated against pH, temperature and chaotropic agent; urea. The results show that cross-linked peroxidase was significantly more stable as compared to soluble counterparts. The reusability study of immobilized enzyme preparation was also performed to use the immobilized preparation up to the industrial level.